Mechanical characterisation of novel polyethylene-based nanocomposites - Alghamdi, Abdulaziz (2014)
Polymer-based nanocomposites are of significant current research interest owing to their outstanding mechanical properties, light weight, processability and low cost. They are also increasingly being considered for a range of industrial applications, including packaging, fuel tanks, gas barriers and high performance films. Ultra-high molecular weight polyethylene (UHMWPE) is already used in various applications, such as lightweight body armour because of its high impact resistance with light weight and total joint replacement due to its high wear resistance. However, a broader use of UHMWPE is limited by the complexity and cost of the manufacturing process, which can be attributed to its high viscosity at processing temperatures. The processability of UHMWPE can be improved by blending with a compatible, lower molecular weight polymer, however, this inevitably results in a reduction in some of the useful properties, such as impact resistance. In this work the potential of adding nano-fillers to such blends to create a range of nanocomposite polymers with the advantages of easy processability and enhanced properties is investigated. The overall aim of this research was to investigate the effect of processing method, strain rate, nanoparticle type and content on the morphological, thermal and mechanical properties of a family of novel polyethylene-based nanocomposites. Polymer nanocomposites of blended UHMWPE and high density polyethylene (HDPE) reinforced with carbon black (CB), carbon nanotubes (CNTs) or inorganic clay were prepared using conventional processing techniques. After initial experiments into the effects of processing parameters, two sets of processing parameters were selected that gave different blend morphology in order to investigate the effect of this on the blend properties and nanofiller dispersion. Characterization of the pure, blended and nanocomposite materials was achieved by the application of combination of experimental techniques. Tensile testing was carried out to characterise the effect of processing method, strain rate, ambient temperature, nanoparticle type and content on the stress-strain behaviour and also to study heat generation during plastic deformation at high strain rates. Depth sensing indentation (DSI) tests were carried out to characterise the effect of processing method, ambient temperature, nanoparticle type and content on the near-surface properties of the materials at a micro-scale under a more complex state of stress that more closely approximates that seen in impact applications. The creep behaviour of the materials was investigated at macro and micro scales at various ambient temperatures. This is important as a weakness of UHMWPE is poor creep resistance and it would be extremely useful if blending or the addition of nanofillers could improve this. A phenomenological model was used to analyse the creep data as this can be usefully used to predict creep performance in service and to aid understanding of the creep phenomena in these materials. The results included in this work are summarised below. Firstly, it was seen that processing parameters had a significant effect on the morphology of the blends, which in turn affected the blend properties and the dispersion of nanoparticles in the blend. Secondly, it was seen that heat generation during plastic deformation of the polyethylene blends and nanocomposites was significantly dependent on morphology, strain rate, nanoparticle type and content. Furthermore, this temperature increase strongly affected the material properties at high strain rates, which is an important consideration if these materials are to be used in high strain rate applications, e.g. as replacement for UHMWPE in helmets and body armour. Thirdly, the macro and micro viscoelastic behaviour of the materials was strongly dependent on the morphology, nanoparticle type and content. A significant increase in creep resistance compared with UHMWPE could be engineered by a careful selection of blend and nanoparticle type and weight fraction. It can be seen, therefore, that a new class of cheap and easy processable polymer nanocomposites have been characterised that can give a range of property sets dependent on the blend processing and nanofiller type and weight fraction. Although certain compromises in property sets are unavoidable, e.g. it is difficult to engineer maximum creep and impact resistance in the same material, this ability to tailor properties could potentially increase the range of applications for these materials and enable better product design.